2011
DOI: 10.4314/ajtcam.v8i2.63199
|View full text |Cite
|
Sign up to set email alerts
|

IN VITRO ANTHELMINTIC EFFECT OF <i>ANOGEISSUS LEIOCARPUS</i> (DC.) GUILL. & PERR. LEAF EXTRACTS AND FRACTIONS ON DEVELOPMENTAL STAGES OF <i>HAEMONCHUS CONTORTUS</i>

Abstract: The anthelmintic effect of acetone leaf extract and fractions of Anogeissus leiocarpus was investigated to determine the relative efficacy of the components as anthelmintic against Haemonchus contortus (Rudolphi). The fractions were obtained by solvent-solvent group separation of the leaf extract. The fractions were evaluated for ovicidal and larvicidal activity by egg hatch inhibition assay and larval development viability assay. Best-fit LC 50 values for egg hatch test were 0.360, 0.316, 0.093, 0.219 and 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The plant has been reported to be used traditionally for the treatment of different ailments including the treatment of diabetic ulcers, general body pain, blood clots, asthma, coughing, jaundice, pile and tuberculosis [10,4,11], Malaria, Trypanosomiasis, Helminthiasis and dysenteric syndrome [12] and also, it is used against stomach infections and fungal infections such as dermatitis and Mycosis [13]. Recent studies have revealed that the plant exhibits a variety of pharmacological activities including Antiplasmodial [14], Antioxidant and hepatoprotective [15,16] Leishmanicidal [17] Anthelmintic [18] Trypanocidal [17,19] antimicrobial [20,21]. The bark and seed of the tree is used for the treatment and prevention of worm infestation in equine species.…”
Section: Introductionmentioning
confidence: 99%
“…The plant has been reported to be used traditionally for the treatment of different ailments including the treatment of diabetic ulcers, general body pain, blood clots, asthma, coughing, jaundice, pile and tuberculosis [10,4,11], Malaria, Trypanosomiasis, Helminthiasis and dysenteric syndrome [12] and also, it is used against stomach infections and fungal infections such as dermatitis and Mycosis [13]. Recent studies have revealed that the plant exhibits a variety of pharmacological activities including Antiplasmodial [14], Antioxidant and hepatoprotective [15,16] Leishmanicidal [17] Anthelmintic [18] Trypanocidal [17,19] antimicrobial [20,21]. The bark and seed of the tree is used for the treatment and prevention of worm infestation in equine species.…”
Section: Introductionmentioning
confidence: 99%